Gastric Intestinal Metaplasia in an Underserved Population in the USA: Prevalence, Epidemiologic and Clinical Features - Tarek Almouradi; Tadd Hiatt; Bashar Attar (Gastroenterology Research and Practice)
Gastric intestinal metaplasia is an important stage in the development of gastric cancer. Limited data is available regarding the prevalence of gastric intestinal metaplasia in the United States. We conducted a retrospective review of esophagogastroduodenoscopies performed in our endoscopy unit between the months of April and October 2010 to evaluate the prevalence and the epidemiologic and endoscopic features of gastric intestinal metaplasia in an underserved population in the United States.